Development of Student Worksheets Based on Project Based Learning on Renewable Energy Material for Senior High School - Sabandiah, Thania; Annisa, Fera; Binti Ahmad, Nur Hidayah (Universitas Islam Negeri Ar-Raniry, 2024)
Based on a questionnaire analysis conducted at SMAN 9 Banda Aceh, it was found that renewable energy material in class uses learning media such as modules, Power Point, Student Worksheets, but teachers only learn from printed books without any practicum. The teaching and learning process still focuses on using non-experimental student worksheets. The aim of this research is to design, determine the feasibility and response of students to Project Based Learning Student Worksheets on renewable energy material for Senior High School. The method used in this research is R&D based on a 4D model. The instruments used in this research consisted of validation sheets and student response sheets. Based on the results of the material expert's assessment, the percentage was 96.61% and the media expert's assessment was 91.07%, including in the very feasible category. Based on the results of the student response sheet to the Student Worksheet based on Project Based Learning on renewable energy material for Senior High School, a percentage result of 94.54% was obtained, including in the very interested category. From this it can be concluded that Student Worksheets based on Project Based Learning are very feasible and practical to use.